IMMOBILIZATION OF STARGENE ?-AMYLASE ON MODIFIED SILICA WITH PROPYL DIETHYLENETRIAMINE-GLUTARALDEHYDE AND ITS ENZYMATIC PROPERTIES - Daniel Despen Sihombing, Zico
?-Amylase (E.C.3.2.1.1) is an industrial enzyme, widely used in the hydrolysis of starch to produce glucose, maltose, and maltodextrin. In industry, the use of enzymes is costly because they cannot be used repeatedly. Enzyme immobilization can be a solution to overcome this problem. The purpose of this study was to immobilize ?-amylase Stargene on propyl diethylenetriamine-glutaraldehyde modified silica and to determine its biochemical properties. In this study, silica was synthesized by the Stober method and further modified with propyl diethylenetriamine followed by glutaraldehyde. Then, the modified silica was used to immobilize ?-amylase Stargene by the covalent attachment method. The biochemical properties of free ?-amylase and immobilized ?-amylase were carried out by the dinitrosalicylic acid (DNS) method, while the amount immobilized protein was determined by the Bradford method. The success of the synthesis of modified silica was determined by infrared (IR) spectroscopy. A typical vibrational absorption band of 1064?1082 cm?1 related to the Si-O-Si vibration was observed, indicating the silica has been formed. For silica- propyl diethylenetriamine-glutaraldehyde, a typical vibration absorption band is obtained at 796?806 cm?1 and 943?947 cm?1 corresponding to the Si-C vibration and a typical vibrational absorption band at wavenumber of 1629?1630 cm?1 for the C=O vibration. Physical changes in the form of color also indicate that modified silica had been formed, which was from white to yellowish cream for silica-propyl diethylenetriamine- glutaraldehyde. The Scanning Electron Microscopy (SEM) image showed the morphology of silica, silica-propyl diethylenetriamine, and silica-propyl diethylenetriamine-glutaraldehyde, which are irregular spheres with sizes of 1.09?2.08, 1.50?2.94, and 2.46?3.97 ?m, respectively. The IR characterization of the immobilized enzyme showed a distinctive vibrational absorption band at 1292 cm?1 from the C-N vibration, indicating ?-amylase had been immobilized on the modified silica matrix. SEM image of spherically bulky immobilized ?-amylase with a size of 11.30?14.50 ?m also showed the success of enzyme immobilization. The optimum pH for free and immobilized ?-amylase was 6.5; the optimum reaction times was 10 minutes for free ?-amylase and 60 minutes for immobilized ?- amylase; and the optimum reaction temperature was 60 °C for both ?-amylase at the optimum concentration of starch solution of 2% w/v. The immobilized ?-amylase still exhibited the activity up to the 7th use and was stable up to 14 days of storage. These results indicate that the immobilized ?-amylase with the propyl diethylenetriamine-glutaraldehyde modified silica are potential to be developed in the starch processing industry.